If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5x = 8 + -3x Solving 6 + -5x = 8 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + -5x + 3x = 8 + -3x + 3x Combine like terms: -5x + 3x = -2x 6 + -2x = 8 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + -2x = 8 + 0 6 + -2x = 8 Add '-6' to each side of the equation. 6 + -6 + -2x = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 8 + -6 -2x = 8 + -6 Combine like terms: 8 + -6 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 5a+7=2a+7 | | -18-9(-6d+3)=-3(-19d+19) | | 5y+9=8y | | 80x^2+68X+12=0 | | (2x-7)=9 | | 18x^2-2=0 | | 8x+10=5x+8 | | 6x-2=34 | | 30+0.25x=59.50 | | 9x+5=7x+6 | | 2(x-5)+3(x-2)=8+7(x-4) | | 25x^2-24x-9=-7x^2+12x-18 | | 4x^2-5=0 | | 8x-7=5x+8 | | 15x^2+8x-16=0 | | 5x-7=7x+5 | | -7(2y+5)+10y=4+18y-19y | | 2b+3=5b+12 | | -74z-81=z-(-33) | | -2p+8=6-(7p+4) | | 6x-2=2x+3 | | 3(1.2x-1)+3.6=4.2 | | 10x-4=2x+10 | | -2x=-30 | | 2-8(-n+3)=(-8n-5)-5 | | -2p+8=6-(7p+2) | | 0.7(x+2)+1.6=17 | | 4y-2=-16-3y | | 10+18n-15n=5(17n+2) | | 0.3(x-0.2)=0.6 | | 5x^2-3x+3=-2x^2+3 | | 2(3ax-2y)-6ax=3(-ax+2y) |